2000
DOI: 10.1016/s0022-0981(00)00201-x
|View full text |Cite
|
Sign up to set email alerts
|

Postlarval chromatophores as an adaptation to ultraviolet radiation

Abstract: It is now well established that ultraviolet radiation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 40 publications
2
16
1
Order By: Relevance
“…Larval distribution under different sea conditions should be further investigated. Recent studies have shown that the development of large chromatophores on larval structures provides an efficient protection against ultraviolet radiation in epineustonic invertebrate larvae (Miner et al 2000). In addition to their dark and thick larval shell, chromatophores are well developed in the foot of C. concholepas competent larvae (DiSalvo 1988), which might help protect competent larvae from harmful UV radiation.…”
Section: Day-night Variation-mentioning
confidence: 99%
“…Larval distribution under different sea conditions should be further investigated. Recent studies have shown that the development of large chromatophores on larval structures provides an efficient protection against ultraviolet radiation in epineustonic invertebrate larvae (Miner et al 2000). In addition to their dark and thick larval shell, chromatophores are well developed in the foot of C. concholepas competent larvae (DiSalvo 1988), which might help protect competent larvae from harmful UV radiation.…”
Section: Day-night Variation-mentioning
confidence: 99%
“…Both the deep-dwelling nature of these copepods (mostly deeper than 100 m) and the darker color at night support this explanation. Yet there is also evidence that chromophore expansion does not necessarily enhance visual predation in other marine invertebrates (Morgan and Christy 1996), perhaps because chromophores also serve other functions, such as thermoregulation (Miner et al 2000). In any case, such diel changes in pigmentation are an important consideration in examining trade-offs between visual predation and UV damage.…”
mentioning
confidence: 99%
“…In order to evoke a fast response, relatively high intensity of PAR was needed, but intensities likely to occur under sea ice also caused a response (UV-experiment control). Pigment dispersal due to exposure to visible light (PAR) is a common phenomenon and has been shown to occur in various crustacean species, mostly decapods (Perkins 1928;Brown and Sandeen 1948;Pautsch 1953;Rao 1966;Barnwell 1968;Coohill et al 1970;Johnson 1974;Miner et al 2000;Auerswald et al 2008). Apherusa glacialis showed an increase in the CI following both higher light intensities and longer exposure times.…”
Section: Photoprotectionmentioning
confidence: 99%
“…However, there are limits to the color change that can be achieved, which will affect the ability of the animal to express an optimal phenotype in a given situation. Such fitness costs are the associated physiological costs, as pigment movement is energy demanding (Miner et al 2000;Boyle and McNamara 2008). The only indication regarding such costs in A. glacialis was that animals tended to aggregate the pigments in their chromatophores when showing obvious signs of decreased activity or shortly before death, probably due to physiological stress.…”
Section: Photoprotection Versus Crypsis-a Trade-offmentioning
confidence: 99%
See 1 more Smart Citation